Job polarization: Evidence for Türkiye. - Gülser, Evren; Yılmaz, Ensar (International Labour Review, 2026)
This article investigates job polarization in Türkiye from 2012 to 2022, analyzing shifts in employment across occupations characterized by abstract, routine, and manual tasks. Using detailed microdata from the Household Labour Force Survey (HLFS) and the Programme for the International Assessment of Adult Competencies (PIAAC), the study finds a U-shaped employment pattern with growth in both low- and high-skill jobs and a decline in middle-skill routine occupations, consistent with the routinization hypothesis driven by technological change, rising educational attainment, and increased female labor force participation. The analysis reveals that within-industry changes, rather than sectoral shifts, primarily drive polarization, and that computer experience is positively associated with abstract tasks but negatively with routine and manual tasks. Despite clear job polarization, wage polarization is not observed, likely due to Türkiye’s active minimum wage policies since 2016, which have compressed wage dispersion. The study also highlights the role of demographic factors, especially the rising participation of women in both high- and low-wage occupations, and suggests limited intergenerational occupational mobility linked to parental education.